Validity and reliability of an on-bike sensor system for the determination of aerodynamic drag in cycling - Hopker, J. G.; Barnes, C.; Fennell, C. R. J.; Gibson, S. (European Journal of Sport Science, 2025)
Cycling performance is strongly influenced by aerodynamics, with most resistive drag forces being attributed to the rider. The Body Rocket device (BR) is an on-bike sensor system that uses the same load cell technology as a wind tunnel, directly measuring real-time aerodynamic resistance (CdA) from the rider. This study aimed to measure the validity and reliability of CdA measures from BR in two experiments. In Experiment 1, validity of BR was assessed in wind tunnel with a rod and discs of known diameter attached to the end change CdA by a known amount. Experiment 2, examined the validity and reliability of BR in a 250m indoor velodrome. Ten cyclists performed 7 identical efforts at ~40 km/h for 10 laps of the velodrome, the first 4 to assess validity with the same rod and discs used in the wind tunnel, with the remaining 3 without changes in resistance or the riders changing position to assess reliability. Validity results demonstrated BR measured CdA to be strongly correlated with calculated CdA from the disc addition (r = 0.99), with the smallest identified changes being 0.002 m2 across wind tunnel and velodrome. Good agreement was found between theoretical and measured CdA with varying disc sizes (95% limits of agreement = -0.012 to 0.009 m2). A high level of reliability was demonstrated during Experiment 2 with strong intraclass correlation (0.99) and small coefficient of variation (1.67%). Findings of this study demonstrate BR is a valid and reliable device for measuring real-time CdA during cycling in an indoor velodrome.